NaSrMn2F7, NaCaFe2F7, and NaSrFe2F7: novel single crystal pyrochlore antiferromagnets. (22nd November 2016) - Sanders, M B; Krizan, J W; Plumb, K W; McQueen, T M; Cava, R J
Abstract: The crystal structures and magnetic properties of three previously unreported A2 B2 F7 pyrochlore materials, NaSrMn2 F7, NaCaFe2 F7, and NaSrFe2 F7 are presented. In these compounds, either S   =  2Fe 2+ or S   =  5/2Mn 2+ is on the B site, while nonmagnetic Na and Ca (Na and Sr) are disordered on the A site. The materials, which were grown as crystals via the floating zone method, display high effective magnetic moments and large Curie–Weiss thetas. Despite these characteristics, no ordering transition is detected. However, freezing of the magnetic spins, characterized by peaks in the susceptibility or specific heat, is observed at very low temperatures. The empirical frustration index, f   =  − θ CW / T f, for the materials are 36 (NaSrMn2 F7 ), 27 (NaSrFe2 F7 ), and 19 (NaCaFe2 F7 ). AC susceptibility, DC susceptibility, and heat capacity measurements are used to characterize the observed spin glass behavior. The results suggest that the compounds are frustrated pyrochlore antiferromagnets with weak bond disorder. The magnetic phenomena that these fluoride pyrochlores exhibit, in addition to their availability as relatively large single crystals, make them promising candidates for the study of geometric magnetic frustration.